Dampak Tuntutan Perubahan Kurikulum terhadap Kualitas Pendidikan SDN 26 Rimbo Kaluang - Apriliani, Wilda; Kustati, Martin; Sepriyanti, Nana (ALSYS, 2025)
Curriculum change is a form of educational innovation aimed at addressing global challenges and local needs. This study seeks to analyze the impact of the transition from the 2013 Curriculum to the Kurikulum Merdeka on the quality of education at SDN 26 Rimbo Kaluang. Employing a qualitative approach with a case study method, the research involved teachers, students, and parents as subjects. Data were collected through interviews, observations, and documentation, and were analyzed thematically. The findings indicate that the implementation of the Kurikulum Merdeka has enhanced student participation and fostered a more interactive and contextual learning environment. Nevertheless, challenges persist, including limited teacher understanding of the new curriculum, students’ readiness to adapt, and low parental involvement. The study concludes that while the Kurikulum Merdeka holds positive potential for improving educational quality, its success depends on systemic preparedness and sustained support. The implications of these findings highlight the need for intensive teacher training, adaptive student support, and strengthened school-parent partnerships to achieve a holistic and sustainable educational transformation.